Book Review: Baja California’s coastal landscapes revealed: excursions in geologic time and climate change, by Markes E. Johnson, 2021. The University of Arizona Press, Tucson, 237 pages. Paperback: price 22.95, ISBN 978-0-8165-4252-9. - Ruban, Dmitry A. (Geologos, 2021)
Book Review: Baja California’s coastal landscapes revealed: excursions in geologic time and climate change, by Markes E. Johnson, 2021. The University of Arizona Press, Tucson, 237 pages. Paperback: price 22.95, ISBN 978-0-8165-4252-9.